Hatching Characteristics of Japanese Quail Eggs in a Tropical Environment - Daikwo, S.I.; Dim, N.I.; Momoh, M.O. (International Journal of Poultry Science, 2011)
A study to evaluate hatching characteristics of incubated Japanese quail eggs in Nigeria was conducted. A total of 1,116 eggs were incubated in 3 batches in a still-air kerosene incubator. The results showed that mean early and late embryonic mortality on the basis of fertile eggs were 18.59±1.85 and 9.89±1.31%, respectively. Mean fertility, hatchability of fertile eggs, hatchability of total eggs set and weight of newly hatched chicks were 85.41±1.25%, 71.52±1.94%, 61.31±1.93% and 6.47±0.10 g, respectively. Hatching chick weight was found positively and significantly (p<0.001) correlated with egg weight (r = 0.96), egg length (r = 0.79) and egg width (r = 0.74). Generally, there was negative correlation between embryo mortality (Early and Late) and external egg quality traits considered. It was concluded that the Japanese quails used in this study have high reproductive efficiency and the still-air kerosene incubator used is recommended for use in rural areas where electricity is irregular or not available to hatch quail eggs.